The Effect of Luting Agents and Ceramic Thickness on the Color Variation of Different Ceramics against a Chromatic Background - Azevedo Cubas, Gloria Beatriz de; Camacho, Guilherme Brião; Demarco, Flávio Fernando; Pereira-Cenci, Tatiana (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to assess the influence of various ceramic thicknesses and luting agents on color variation in five ceramic systems. Methods: Fifteen disc-shaped ceramic specimens (11 mm diameter; shade A3) were fabricated with each of the six veneering ceramics tested, with 1, 1.5, or 2 mm thickness (n=5). Resin composite discs (Z-250, shade C4) were used as bases to simulate a chromatic background. The cementation of the veneers was carried out with an opaque resin-based cement (Enforce, shade C4), a resin-based cement (Enforce, shade A3), or without cement (C4, control group). Color differences (ΔE*) were determined using a colorimeter. Three-way ANOVA was used to analyze the data, followed by a Tukey post-hoc test (α=.05). Results: The L*a*b* values of the ceramic systems were affected by both the luting agent and the ceramic thickness (P<.05). In general, there was no difference between the control group and the group using the resin-based cement. The use of an opaque luting agent resulted in an increase of the color coordinates a*, b*, L*, producing differences in ΔE* values for all ceramics tested, regardless of the thickness (P<.05). For the 2-mm thick veneers, higher values in the color parameters were obtained for all ceramics and were independent of the luting agent used. Conclusions: The association of 2-mm thickness with opaque cement presented the strongest masking ability of a dark colored background when compared to a non-opaque Lutinging agent and the other thicknesses tested. (Eur J Dent 2011;5:245-252)
Keywords: Ceramics; Luting agents; Thickness; Color